La migración venezolana en el discurso periodístico (Ensayos) - López Montenegro, Ligia Adriana (2021)
The social, political and economic conditions of Venezuela have caused its population to have made the decision to emigrate to other nations, including Ecuador. As it is an issue that affects different social spheres, it has been addressed by different media. Within the present study, it was analyzed how the journalistic discourse of the newspaper La Nación is constructed, in relation to the migratory process of the Venezuelan population to Ecuador and how this influences the creation of social representations? The study methodology focused on the application of the Technical Communicational Version, in order to delve into the problem, the context and the actors around the communication medium, in addition, the principles of critical discourse analysis were taken into account to identify the representations present in the journalistic discourse related to the immigration issue, a total of 4 informative notes were analyzed. The results showed that the approach, language, intentionality and discursive production of the migration issue will generate in the audience the creation of biased social representations about the reality of migrants, making them invisible and ignoring the context of their situation. For this reason, it is important that the media have instruments that help them produce an informative production that allows the audience to understand migration from its different dimensions.